Impact of subspecialty training on management of laryngopharyngeal reflux: results of a worldwide survey - ENVER, NECATİ (SPRINGER, 2021)
Objective To study the management of laryngopharyngeal reflux (LPR) among the subspecialties of practicing otolaryngology-head and neck surgeons and their trainees. Methods A survey was sent to over 8000 otolaryngologists (OTOHNS) over 65 countries, utilizing membership lists of participating otolaryngological societies. The outcomes were answers to questions regarding LPR knowledge and practice patterns, and included queries about its definition, prevalence, clinical presentation, diagnosis, and treatment. Results Of the 824 respondents, 658 practiced in one specific otolaryngologic subspecialty. The symptoms and findings thought to be the most related to LPR varied significantly between subspecialists. Extra-laryngeal findings were considered less by laryngologists while more experienced OTOHNS did not often consider digestive complaints. Compared with colleagues, otologists, rhinologists and laryngologists were less aware of the involvement of LPR in otological, rhinological and laryngological disorders, respectively. Irrespective of subspecialty, OTOHNS consider symptoms and signs and a positive response to empirical therapeutic trial to establish a LPR diagnosis. Awareness regarding the usefulness of impedance pH-studies is low in all groups. The therapeutic approach significantly varies between groups, although all were in agreement for the treatment duration. The management of non-responder patients demonstrated significant differences among laryngologists who performed additional examinations. The majority of participants (37.1%) admitted to being less than knowledgeable about LPR management. Conclusions LPR knowledge and management vary significantly across otolaryngology subspecialties. International guidelines on LPR management appear necessary to improve knowledge and management of LPR across all subspecialties of otolaryngology.
Keywords: Laryngopharyngeal; Laryngitis; Reflux; Gastroesophageal; GERD; Diagnosis; Management; Treatment; Survey